The bispecific B7H3xCD3 antibody CC-3 induces T cell immunity against bone and soft tissue sarcomas - Holzmayer, Samuel J.; Liebel, Kai; Hagelstein, Ilona; Salih, Helmut R.; Märklin, Melanie (Frontiers in Immunology, 2024)
Sarcomas are rare and heterogeneous malignancies that are difficult to treat. Approximately 50% of patients diagnosed with sarcoma develop metastatic disease with so far very limited treatment options. The transmembrane protein B7-H3 reportedly is expressed in various malignancies, including different sarcoma subtypes. In several cancer entities B7-H3 expression is associated with poor prognosis. In turn, B7-H3 is considered a promising target for immunotherapeutic approaches. We here report on the preclinical characterization of a B7-H3xCD3 bispecific antibody in an IgG-based format, termed CC-3, for treatment of different sarcoma subtypes. We found B7-H3 to be expressed on all sarcoma cells tested and expression on sarcoma patients correlated with decreased progression-free and overall survival. CC-3 was found to elicit robust T cell responses against multiple sarcoma subtypes, resulting in significant activation, release of cytokines and effector molecules. In addition, CC-3 promoted T cell proliferation and differentiation, resulting in the generation of memory T cell subsets. Finally, CC-3 induced potent target cell lysis in a target cell restricted manner. Based on these results, a clinical trial evaluating CC-3 in soft tissue sarcoma is currently in preparation.